Implications of the GATS Agreement on Financial Inclusion in Iraq 2018-2022 - Hadi, Huda; Rasheed, Thaer (Journal of Economics and Administrative Sciences, 2025)
The paper attempts to present the time and authority in the period between 2018 and 2022 concerning whether an accession of Iraq to the World Trade Organization under the aegis of GATS would establish an impact on financial inclusion. The objective is to find how service liberalization in conformity with GATS may influence financial inclusion in terms of access, use, and depth of banking services. The paper adopts a descriptive-analytical and deductive approach by considering factors such as banking density, spread of electronic payments, acceptance of mobile transactions, and credit-to-GDP ratio. The findings revealed that financial services liberalization at the GATS level has led to an expansion of digital infrastructures, including ATMs, POS terminals, and mobile payment systems, thereby enhancing banking access and lessening financial exclusion. Still, problems remain, especially in rural areas with insufficient infrastructure, limited trust in financial systems, and financial literacy. In the end, the study points out that while liberalization under GATS can propel the general financial inclusion agenda, restructuring of Iraq alone, working on digital trust, and fostering innovation are essential for Iraq to capitalize on the benefits. This research value-adding lies in making an interconnection between international trade agreements and financial development inside a country and offering a strategic roadmap to policymakers for aligning banking reforms with international standards for inclusive economic development.